2020
DOI: 10.1016/j.cell.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Host-Specific Evolutionary and Transmission Dynamics Shape the Functional Diversification of Staphylococcus epidermidis in Human Skin

Abstract: Highlights d S. epidermidis strains within-individual are diverse and evolved from multiple founders d Strain diversity is shaped by purifying selection and transmission events d Strain admixture can suppress virulence and alter metabolism at a population level d Horizontal gene transfer disseminates antibiotic resistance genes within individuals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
154
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(169 citation statements)
references
References 131 publications
(185 reference statements)
14
154
0
1
Order By: Relevance
“…This may also explain why one isolate, 9 c , appeared to be phylogenetically more similar to skin isolates than the other fecal isolates. One recent study by Zhou et al (2020), reported substantial transmission of S. epidermidis strains between facial sites and other skin sites, particularly the hands and antecubital fossa, across all participants. Although no fecal samples were screened in that study, it is possible that touching of the face and mouth area may offer a route of transmission from the skin to the gut.…”
Section: Discussionmentioning
confidence: 93%
“…This may also explain why one isolate, 9 c , appeared to be phylogenetically more similar to skin isolates than the other fecal isolates. One recent study by Zhou et al (2020), reported substantial transmission of S. epidermidis strains between facial sites and other skin sites, particularly the hands and antecubital fossa, across all participants. Although no fecal samples were screened in that study, it is possible that touching of the face and mouth area may offer a route of transmission from the skin to the gut.…”
Section: Discussionmentioning
confidence: 93%
“…While pathogen epidemiology has long relied on comparative genomics among up to tens of thousands of isolates, it has only recently become efficient to carry out large-scale isolation of commensal organisms from human populations or individuals [170,171]. Doing so, however, opens up the ability to identify strain-level differences among isolates of the same species among individuals [12,13,172,173], within an individual microbiome at different spatial locations [81,174], or over time [170,175]. Once isolated, of course, such microbial strains can be characterized by any number of standard methods, including differences among growth curves or media, chemical (e.g., antimicrobial) resistance, metabolic flux profiling, or amplicon or shotgun sequencing.…”
Section: Strain Identification From Microbial Community Sequencingmentioning
confidence: 99%
“…We postulate that S. epidermidis, through recognition of TLR2/TLR1 heterodimers on cutaneous GD T cells, regulates not only Th1 responses but also cytotoxic mediators such as P-2. The recognition of TLR2/TLR1 heterodimers may even be strain specific (12) warranting further studies on the mechanisms of P-2 induction by S. epidermidis CCN021.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common members of the healthy cutaneous microbiome is Staphylococcus epidermidis. S. epidermidis stimulates antimicrobial peptide production by skin cells (4)(5)(6)(7)(8)(9)(10)(11), which may provide protection against pathogenic bacteria (4,5,(10)(11)(12). Recent studies reported that colonization of mouse skin with S. epidermidis induced commensal-specific tissue (skin)-resident memory T cells that demonstrated immunoregulatory and tissue repair properties.…”
Section: Introductionmentioning
confidence: 99%